Three new species of the sucking louse genus Hoplopleura (Phthiraptera: Anoplura: Hoplopleuridae) from rodents (Mammalia: Rodentia: Muridae) in northern Australia - Weaver, Haylee J. (Zootaxa, 2017)
Three new species of the rodent louse genus Hoplopleura (Anoplura: Hoplopleuridae) are described and illustrated from Australia: H. melomydis new species from Melomys burtoni (Muridae: Hydromyini, grassland melomys) and M. capensis (Muridae: Hydromyini, Cape York melomys) from Queensland; H. notomydis new species and H. setosa new species from Notomys alexis (Muridae: Hydromyini, spinifex hopping mouse) from the Northern Territory. These new louse species are the first lice recorded from each of the three host rodent species.